Infection‐related hospital admissions after transrectal biopsy of the prostate. (25th January 2013) - Sanders, Andrew; Buchan, Nicholas
Abstract Background Urosepsis is the most common complication requiring hospital admission after transrectal biopsy of the prostate. This study aims to assess the local incidence and causative organisms of hospital admissions with urosepsis after transrectal ultrasound‐guided prostate (TRUS) biopsy. As morbidity is high, treatment must be commenced empirically prior to cultures. A review of bacterial antibiotic susceptibilities was undertaken to guide optimal treatment of post‐biopsy urosepsis. Methods A total of 1421 patients underwent TRUS biopsy in a single city over a 2‐year period. All patients received prophylactic antibiotics prior to the procedure. A retrospective review of a prospectively collated database was performed in all patients admitted to Christchurch Hospital, the only acute admitting hospital in Christchurch, with infection within 30 days after biopsy. Hospital admission records were reviewed, including urine and blood culture results. Results Forty patients (2.8%) were admitted with infection after the biopsy, the majority occurring within the first week after procedure and four required intensive care unit (ICU) admission (10%). The most common organism isolated on urine and blood cultures was Escherichia coli. Significant E. coli resistance was seen to fluoroquinolones, amoxicillin and trimethoprim. Conclusion Rates of infection after TRUS biopsy and antibiotic resistance are increasing internationally. Treatment for urosepsis should be aggressive as 10% of those patients admitted required ICU admission. TRUS biopsy with ciprofloxacin prophylaxis led to infectious complications comparable with other international reports and appears to remain an appropriate prophylactic antibiotic of choice. Infections requiring hospital admission were all susceptible to a combination of ceftriaxone and gentamicin, and would be an effective initial antibiotic of choice.